تعليم اللغة العربية باستخدام الطريقة المباشرة لترقية مهارة الكلام دراسة عن بعد بوسيلة واتساب وزووم (لدى تلميذات الصف الأول بمدرسة كتاب ابن عباس تانجيرانج) - Siti Fatimah (Rayah Al-Islam, 2021)
الملخص تعليم اللغة العربية الذي أجريَ بمدرسة كتاب ابن عباس هو نشاط تعليمي يقوم به المعلمون لتزويد الطلاب بهدف أن يكونوا قادرين على فهم دينهم بشكل صحيح، وتغيير السلوك وزيادة المعرفة، وخاصة الأمور المتعلقة باللغة العربية والقدرة على التحدث وفهم اللغة العربية في شكل شفوي وكتابي. وهدف تعليم اللغة العربية لهذا المستوى ليكون عند الطلاب القدرة في اللغة العربية مثل صاحب اللغة مثل أطفال العرب الذين يعيشون في الدولة العربية. حتى يجعلوا مستواهم قريبا من هؤلاء فلابد أن يكون المدرس هو ناطقا للغة العربية لأن الطلاب سيأخذون اللغة من المدرس، كيف المدرس يعبر، كيف طريقة كلامه وتعبيره، ولهذا ليس شرطا كون المدرس ناطقا للعربية ولكنه أفضل. أو غير ناطق مثلا إندونيسي ولكن عنده القدرة العالية في اللغة العربية. ومشكلة هذا البحث هي: (١)كيف تنفيذ تعليم اللغة العربية باستعمال وسائل التواصل وسائطَ التعلم لدى تلميذات الصف الأول بمدرسة كتاب ابن عباس تانجيرانج. (٢) كيف فعالية استعمال طريقة تعليم اللغة العربية بوسائل التواصل عند تلميذات الصف الأول بمدرسة كتاب ابن عباس تانجيرانج. (٣) ما المشكلة التي تواجهها تلميذات الصف الأول بمدرسة كتاب ابن عباس تانجيرانج في تعلم اللغة العربية عن بعد. (٤) ما المشكلة التي تواجهها المدرّسة في تعليمهن. Abstract Teaching Arabic that was conducted at Kuttab Ibnu Abbas School is an educational activity undertaken by teachers to provide students with the goal of being able to properly understand their religion, change behavior and increase knowledge, especially matters related to the Arabic language and the ability to speak and understand Arabic in conversation and written form. And the goal of teaching Arabic to this level is so that students have the ability in the Arabic language like the owner of the language, like the children of Arabs who live in the Arab country. In order to make their level close to those, the teacher must be a native speaker of the Arabic language because the students will take the language from the teacher, how does the teacher express, how does his speech and his expression, and this is not a requirement for the teacher to speak Arabic, but it is better. Or not speaking Indonesian, for example, but he has a high ability in the Arabic language. The problem of this research is: (1) How to implement the teaching of Arabic language using the means of communication and the means of learning among first-grade students at Kitab Ibn Abbas Tangerang School. (2) How effective is the use of the method of teaching the Arabic language by means of communication among first grade pupils at Kitab Ibn Abbas Tangerang School? (3) What is the problem faced by the first graders of Kitab Ibn Abbas Tangerang School in learning Arabic from a distance? (4) What is the problem that the female teacher faces in teaching them?